Ergonomic Exercises to Lower Uric Acid Levels in the Elderly with Gout - Muji Hartinah; Suharti Suharti; Elsa Gusrianti; Santa Novita Yosephin Silalahi (Alliance oh Health Activists (AloHA), 2024)
Ergonomic gymnastics is a practical and effective method to maintain a healthy body. The movements contained in ergonomic gymnastics are movements that are very effective, efficient, and logical because they use a series of movements that have been carried out by humans from the past until now. Ergonomic gymnastic movements are in accordance with the rules of body creation, and are inspired by the